Ion sieve for salt bath purification as well as preparation method and use method of ion sieve
By using a specific composition of ion sieve in the salt bath, the problem of the constant change and non-fall after lithium ion absorption is solved, the glass reinforcement effect and the service life of the salt bath are improved, and the glass appearance quality is ensured.
Patent Information
- Application Number
- CN202311789340.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-12-25
AI Technical Summary
In the prior art, the increase in Li+ in the salt bath leads to an increase in the size defect rate after glass strengthening, and the existing ion sieve is prone to fall off at high temperatures, affecting the appearance of the glass and the service life of the salt bath.
Provide an ion sieve including SiO2, Al2O3, Na2O, ZrO2 and Y2O3. By controlling the composition and preparation method, it ensures that the crystal shape does not change and does not fall off after absorption in a salt bath of 350°C-550°C. Lithium ion absorption efficiency.
It realizes stable absorption of lithium ions in high-temperature salt bath, avoids crystal shape transformation and fall off, improves the glass reinforcement effect and the service life of the salt bath, and ensures the quality of the glass appearance.
Smart Images

Figure CN119219328A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ion sieves, and in particular to an ion sieve for salt bath purification and a preparation method and a use method thereof. Background Art
[0002] During the chemical strengthening process of glass, alkali metal ions with large ionic radius (such as K + 、Na + ) replaces the alkali metal ions with small ionic radius (such as Na + , Li + ), a "crowding effect" is generated within a certain depth range, forming a specific stress distribution, hindering the expansion of microcracks in the glass, thereby achieving the purpose of improving the strength of the glass. At the same time, alkali metal ions with small ion radius will continuously enter the salt bath from the glass, causing Na + , Li + Although Na + , Li + The content of Li in the salt bath is only at the ppm level, but it is enough to seriously hinder the normal chemical strengthening process, resulting in a decrease in the stress level of the subsequent glass after strengthening, a significant decrease in mechanical strength, and the final product performance does not meet the use requirements. + The increase will seriously weaken the degree of lithium-sodium exchange during chemical strengthening of lithium aluminum-silicon glass, resulting in a rapid decrease in the increase in glass size after strengthening, and it is impossible to achieve the glass size deviation range of less than 20μm in mobile phone cover applications, ultimately leading to an increase in the size defective rate of chemically strengthened glass.
[0003] In the prior art, powdered sodium phosphate is added to a salt bath. After the sodium phosphate is dissolved in the salt bath, the phosphate radical reacts with the Li + Form lithium phosphate precipitation to reduce the impurity Li in the salt bath + The content of lithium phosphate can extend the service life of the salt bath. However, lithium phosphate precipitation will make the salt bath turbid, and it will take a long time to clarify before it can be used again. In addition, some lithium phosphate particles will adhere to the surface of the strengthened glass, causing defects in the glass, which is not conducive to the mass production of chemically strengthened glass. In addition, too much lithium phosphate precipitation at the bottom of the salt bath will reduce the effective working area of the salt bath, making it difficult to clean. In the prior art, silicon-based glass ionomer screens are used to absorb the impurities Li in the salt bath. + , thereby extending the service life of the salt bath; however, the surface of the silicon-based glass ion sieve will fall off after long-term use in a high-temperature salt bath, and the shed material is easily adsorbed on the surface of the tempered glass sheet, resulting in a poor appearance of the tempered glass sheet. Summary of the invention
[0004] Based on the above situation, the purpose of the present application is to solve the shortcomings of the existing technical solutions and provide an ion sieve that does not undergo crystal transformation and does not shed fragments after use in a salt bath. It will not contaminate the salt bath, and no fragments will adhere to the surface of the tempered glass to affect the appearance quality of the tempered glass, and has high lithium ion absorption efficiency.
[0005] In a first aspect, the present application provides an ion sieve, which comprises the following components in terms of molar percentage of oxide:
[0006] SiO2 45.0-64.0mol%;
[0007] Al2O3 2.0-16.0mol%;
[0008] Na2O 34.0-45.0mol%;
[0009] ZrO2 0-3.0mol%;
[0010] Y2O3 0-2.0mol%;
[0011] Wherein, after the ion sieve absorbs lithium ions for 0.5h-24h in a salt bath at a temperature of 350°C-550°C, the crystal form of the ion sieve does not change.
[0012] In some embodiments of the present application, after the ion sieve undergoes sodium-lithium ion exchange in any proportion within the range of 350° C.-550° C., the content of crystals in the ion sieve is less than 10 wt %.
[0013] In some embodiments of the present application, the density of the ion sieve is 2.40 g / cm 3 -2.55g / cm 3 .
[0014] In some embodiments of the present application, the ion sieve does not shed fragments after absorbing lithium ions for 0.5h-24h in a salt bath at 350°C-550°C.
[0015] In some embodiments of the present application, the concentration of lithium ions in the salt bath is 50 ppm-400 ppm.
[0016] In a second aspect, the present application provides a method for preparing the above-mentioned ion sieve, comprising: selecting raw material components according to the composition of the ion sieve, mixing them, melting and forming them, and then annealing them to obtain the ion sieve.
[0017] In some embodiments of the present application, the melting temperature is 1300° C.-1650° C., and the melting time is 1 h-24 h.
[0018] In some embodiments of the present application, the annealing temperature is 400° C.-450° C., and the annealing time is 12 h-24 h.
[0019] In a third aspect, the present application provides a composite salt bath additive, which is a mesh container and an alkali metal ion adsorbent filled in the mesh container, and the alkali metal ion adsorbent is an ion sieve as described above or an ion sieve prepared by the preparation method of the above ion sieve; the mesh of the mesh container is greater than 0.15 mm.
[0020] In some embodiments of the present application, the mesh container is at least one of a stainless steel container and a metal container.
[0021] In some embodiments of the present application, the filling rate of the alkali metal ion adsorbent is 20%-80% relative to the volume of the mesh container.
[0022] In some embodiments of the present application, the alkali metal ions adsorbed by the alkali metal ion adsorbent are lithium ions.
[0023] In a fourth aspect, the present application provides the use of the ion sieve as described above, or the ion sieve prepared by the preparation method of the ion sieve as described above, or the composite salt bath additive as described above in salt bath purification.
[0024] In a fifth aspect, the present application provides a method for using the ion sieve as described above or the ion sieve prepared by the preparation method of the ion sieve as described above, comprising:
[0025] Step 1): providing a salt bath to be purified, wherein the salt bath contains lithium ions;
[0026] Step 2): adding an ion sieve to the salt bath to be purified;
[0027] Step 3): After the ion sieve has reacted in the salt bath to be purified for a certain period of time, it is taken out.
[0028] In some embodiments of the present application, the added amount of the ion sieve is 0.5wt%-5.0wt% of the mass of the salt bath to be purified.
[0029] In some embodiments of the present application, the temperature of the salt bath is 350°C-550°C.
[0030] In some embodiments of the present application, the concentration of lithium ions in the salt bath is 50 ppm-400 ppm.
[0031] In some embodiments of the present application, the ion sieve reacts in the salt bath to be purified for 3 hours to 24 hours.
[0032] In some embodiments of the present application, the absorption efficiency of the ion sieve is 50%-95%.
[0033] In some embodiments of the present application, when the lithium ion concentration of the salt bath to be purified is 50ppm-400ppm, the addition amount of the ion sieve is 0.50wt%-5.00wt% of the mass of the salt bath to be purified, and the reaction time of the ion sieve in the salt bath to be purified is 3h-24h, and the absorption efficiency of the ion sieve is 50%-95%.
[0034] In a sixth aspect, the present application provides a method for using the composite salt bath additive as described above, comprising:
[0035] Step 1): providing a salt bath to be purified, wherein the salt bath contains lithium ions;
[0036] Step 2): adding a composite salt bath additive to the salt bath to be purified;
[0037] Step 3): After the composite salt bath additive has reacted in the salt bath to be purified for a certain period of time, it is taken out.
[0038] In some embodiments of the present application, the added amount of the alkali metal ion adsorbent in the composite salt bath additive is 0.5wt%-5.0wt% of the mass of the salt bath to be purified.
[0039] In some embodiments of the present application, the filling rate of the alkali metal ion adsorbent is 20%-80% relative to the volume of the mesh container.
[0040] In some embodiments of the present application, the temperature of the salt bath is 350°C-550°C.
[0041] In some embodiments of the present application, the concentration of lithium ions in the salt bath is 50 ppm-400 ppm.
[0042] In some embodiments of the present application, the composite salt bath additive reacts in the salt bath to be purified for 3 hours to 24 hours.
[0043] In some embodiments of the present application, the absorption efficiency of the composite salt bath additive is 50%-95%.
[0044] In some embodiments of the present application, when the lithium ion concentration of the salt bath to be purified is 50ppm-400ppm, the added amount of the alkali metal ion adsorbent is 0.50wt%-5.00wt% of the mass of the salt bath to be purified, and the filling rate of the alkali metal ion adsorbent is 20%-80% relative to the volume of the mesh container; the reaction time of the composite salt bath additive in the salt bath to be purified is 3h-24h, and the absorption efficiency of the composite salt bath additive is 50%-95%.
[0045] In the seventh aspect, the present application also provides a chemical strengthening process for lithium-containing microcrystalline glass, which includes the following steps: adding the ion sieve described above in the present application or the ion sieve prepared by the above-mentioned ion sieve preparation method or the above-mentioned composite salt bath additive to the salt bath for chemically strengthening the lithium-containing microcrystalline glass.
[0046] Compared with the prior art, this application has the following beneficial effects:
[0047] 1. The present application controls the ion sieve to absorb lithium ions for 0.5h-24h in a salt bath at a temperature of 350°C-550°C, and the crystal content does not exceed 10wt% with a slight change, so that the crystal form will not change, and no fragments will fall off, the salt bath will not be polluted, and no fragments will adhere to the surface of the tempered glass to affect its appearance quality, and it has a high lithium ion adsorption efficiency.
[0048] 2. The present application controls the mesh size of the mesh container of the composite salt bath additive to be greater than 0.15 mm, thereby achieving that the composite salt bath additive does not affect the actual adsorption effect of the ion sieve on the salt bath purification, and has a high adsorption efficiency for lithium ions; at the same time, it can prevent the ion sieve from affecting the appearance quality of the tempered glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0050] Figure 1 The initial XRD (X-ray diffraction) patterns of the ion sieves of Example 1, Example 5, Comparative Example 1 and Comparative Example 4 are shown.
[0051] Figure 2 The XRD spectra of the ion sieves of Example 1, Example 5, Comparative Example 1 and Comparative Example 4 after absorbing lithium ions in a 480° C. salt bath for 8 hours.
[0052] Figure 3This is the appearance of the ion sieve in Example 1 after absorbing lithium ions in a 480°C salt bath for 8 hours.
[0053] Figure 4 This is the appearance of the ion sieve in Example 6 after absorbing lithium ions in a 480°C salt bath for 8 hours.
[0054] Figure 5 This is the appearance of the ion sieve in Comparative Example 2 after absorbing lithium ions in a 480°C salt bath for 8 hours.
[0055] Figure 6 This is the appearance of the ion sieve in Comparative Example 3 after absorbing lithium ions in a 480°C salt bath for 8 hours.
[0056] Figure 7 This is the appearance of the ion sieve in Comparative Example 5 after absorbing lithium ions in a 480°C salt bath for 8 hours.
[0057] Figure 8 This is the appearance of the ion sieve in Comparative Example 6 after absorbing lithium ions in a 480°C salt bath for 8 hours.
[0058] Fig. 9 This is a polarizing microscope image of the surface of the chemically strengthened glass obtained after adding the ion sieve of Example 2 to the salt bath.
[0059] Fig.10 This is a polarizing microscope image of the surface of the chemically strengthened glass obtained after adding the ion sieve of Comparative Example 4 into the salt bath.
[0060] Fig.11 This is a polarizing microscope image of the surface of the chemically strengthened glass obtained after adding the composite salt bath additive A3 to the salt bath.
[0061] Fig.12 This is a polarizing microscope image of the surface of the chemically strengthened glass obtained after adding the composite salt bath additive B3 to the salt bath. DETAILED DESCRIPTION
[0062] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0063] In a first aspect, the present application provides an ion sieve, which comprises the following components in terms of molar percentage of oxide:
[0064] SiO2 45.0-64.0mol%;
[0065] Al2O3 2.0-16.0mol%;
[0066] Na2O 34.0-45.0mol%;
[0067] ZrO2 0-3.0mol%;
[0068] Y2O3 0-2.0mol%;
[0069] Wherein, after the ion sieve absorbs lithium ions for 0.5h-24h in a salt bath at a temperature of 350°C-550°C, the crystal form of the ion sieve does not change.
[0070] In some embodiments of the present application, the content of SiO2 in the ion sieve can be 45.0mol%, 46.0mol%, 47.0mol%, 48.0mol%, 49.0mol%, 50.0mol%, 51.0mol%, 52.0mol%, 53.0mol%, 54.0mol%, 55.0mol%, 56.0mol%, 57.0mol%, 58.0mol%, 59.0mol%, 60.0mol%, 61.0mol%, 62.0mol%, 63.0mol%, 63.10mol%, 64.0mol% or any two of the above values as endpoints. SiO2 is a glass network forming oxide, which is used to form a skeleton of the ion sieve network structure composed of covalent bonds. The selection of its composition and content directly affects the adsorption performance of the ion sieve network structure and the thermal stability of the ion sieve in a high temperature environment. Too low SiO2 content will lead to poor formability of the ion sieve, while too high SiO2 content will lead to higher viscosity of the glass, making it difficult to melt the glass.
[0071] In some embodiments of the present application, the content of Al2O3 in the ion sieve can be 2.0mol%, 3.0mol%, 4.0mol%, 5.0mol%, 6.0mol%, 7.0mol%, 8.0mol%, 9.0mol%, 10.0mol%, 11.0mol%, 12.0mol%, 13.0mol%, 14.0mol%, 15.0mol%, 16.0mol% or a value within the range formed by any two of the above values as endpoints. Al2O3 is a component of the network architecture, and is also beneficial to enhancing the lithium ion absorption rate during the adsorption of lithium ions by the ion sieve, and improving the ion sieve's resistance to decomposition at high temperatures, but too high alumina content will make it difficult to form the ion sieve.
[0072] In some embodiments of the present application, the content of Na2O in the ion sieve can be 34.0mol%, 35.0mol%, 36.0mol%, 37.0mol%, 38.0mol%, 39.0mol%, 40.0mol%, 41.0mol%, 42.0mol%, 43.0mol%, 44.0mol%, 45.0mol% or any two of the above values as endpoints. Na2O is a network exo-oxide formed by glass, and its content directly affects the ability of the ion sieve to adsorb lithium ions, but too high a content of Na2O may cause the chemical stability of the ion sieve to decrease.
[0073] In some embodiments of the present application, the content of ZrO2 in the ion sieve can be 0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 3.0 mol% or a value within a range formed by any two of the above values as endpoints. ZrO2 can improve the chemical stability and thermal stability of the ion sieve, but the tendency of crystallization will increase when the ZrO2 content is high.
[0074] In some embodiments of the present application, the content of Y2O3 in the ion sieve can be 0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol% or a value within a range formed by any two of the above values as endpoints. Y2O3 can improve the hardness and chemical stability of the ion sieve, but the tendency of crystallization will increase when the content of Y2O3 is high.
[0075] In some embodiments of the present application, the crystal content of the ion sieve before absorbing lithium ions in the salt bath is less than 10wt%; wherein the crystal content is measured by the proportion of the crystal phase peak area in the XRD spectrum of the ion sieve. In some embodiments of the present application, the crystal content of the ion sieve before absorbing lithium ions in the salt bath is 0.5-9.0wt%, 0.5-7.0wt%, 0.5-5.0wt%; further, it can be 0.5wt%, 0.8wt%, 1.5wt%, 2.8wt%, 3.7wt%, 5.0wt%, 7.0wt%, 9.0wt%, 10wt% or a value within the range formed by any two of the above values as endpoints.
[0076] In some embodiments of the present application, after the ion sieve undergoes sodium-lithium ion exchange in any proportion within the range of 350°C-550°C, the content of crystals in the ion sieve is less than 10wt%; wherein the crystal content is measured by the proportion of the crystalline phase peak area in the XRD spectrum of the ion sieve. In some embodiments of the present application, after the ion sieve undergoes sodium-lithium ion exchange in any proportion within the range of 350°C-550°C, the content of crystals in the ion sieve can be 0.5-9.0wt%, 0.5-7.0wt%, 0.5-5.0wt%; further, it can be 0.5wt%, 0.8wt%, 1.5wt%, 2.8wt%, 3.7wt%, 5.0wt%, 7.0wt%, 9.0wt%, 10wt% or a value within the range formed by any two of the above values as endpoints. Without being limited to any theory, the inventors believe that when the ion sieve absorbs impurity lithium ions in the salt bath, although Na + and Li + ion exchange; however, since the crystal content of the ion sieve before and after absorbing lithium ions is less than 10wt%, the change is small, and the crystal form will not change. Therefore, the structure of the ion sieve before and after absorbing lithium ions is stable, and no fragments will fall off.
[0077] In some embodiments of the present application, after the ion sieve absorbs lithium ions for 0.5h-24h in a salt bath at 350°C-550°C, the crystal form of the ion sieve does not change. In some embodiments of the present application, the temperature of the salt bath may be 350°C, 360°C, 370°C, 380°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or any two of the above values as endpoints. In some embodiments of the present application, the time for lithium ion absorption can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 16h, 14h, 18h, 20h, 22h, 24h or a value within the range formed by any two of the above values as endpoints. The present application does not particularly limit the type of salt bath, as long as it contains lithium ions, wherein the impurity ions are mainly lithium ions; for example, it can be a salt bath containing NaNO3, a salt bath containing KNO3, or a mixed salt bath containing NaNO3 and KNO3 in the presence of lithium ions. In some embodiments of the present application, the concentration of lithium ions in the salt bath is 50ppm-400ppm.
[0078] In some embodiments of the present application, the ion sieve absorbs lithium ions for 0.5h-24h in a salt bath at 350°C-550°C without shedding fragments. In some embodiments of the present application, the temperature of the salt bath may be 350°C, 360°C, 370°C, 380°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or any two of the above values as endpoints. In some embodiments of the present application, the time for lithium ion absorption can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 16h, 14h, 18h, 20h, 22h, 24h or a value within the range formed by any two of the above values as endpoints. The present application does not particularly limit the type of salt bath, as long as it contains lithium ions, wherein the impurity ions are mainly lithium ions; for example, it can be a salt bath containing NaNO3, a salt bath containing KNO3, or a mixed salt bath containing NaNO3 and KNO3 in the presence of lithium ions. In some embodiments of the present application, the concentration of lithium ions in the salt bath is 50ppm-400ppm.
[0079] In some embodiments of the present application, the concentration of lithium ions in the salt bath may be 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 120 ppm, 140 ppm, 150 ppm, 160 ppm, 170 ppm, 180 ppm, 190 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, or a value within a range formed by any two of the above values as endpoints.
[0080] In some embodiments of the present application, the density of the ion sieve is 2.40 g / cm 3 -2.55g / cm 3 In some embodiments of the present application, the density of the ion sieve may be 2.40 g / cm 3 , 2.41g / cm 3 , 2.42g / cm 3 , 2.43g / cm 3 , 2.44g / cm 3 , 2.45g / cm 3 , 2.46g / cm 3 , 2.47g / cm 3 , 2.48g / cm 3 , 2.49g / cm 3 , 2.50g / cm 3 , 2.51g / cm3 , 2.52g / cm 3 , 2.53g / cm 3 , 2.54g / cm 3 , 2.55g / cm 3 Or a value within the range formed by any two of the above values as endpoints.
[0081] In a second aspect, the present application provides a method for preparing the above-mentioned ion sieve, comprising: selecting raw material components according to the composition of the ion sieve, mixing them, melting and forming them, and then annealing them to obtain the ion sieve.
[0082] The present application does not have any particular restrictions on the method of forming. For example, the molten liquid may be injected into a mold or a cast iron platform for forming. After the annealing treatment of the present application, post-processing such as cutting and polishing may be performed to process the ion sieve into a shape commonly found in this field. For example, it may be one or more of granular, sheet-like, porous and / or plate-like. The present application does not have any particular restrictions on the size of the shape of the ion sieve processing. For example, the cutting size may be 50mm×50mm×0.7mm.
[0083] In the preparation method of the ion sieve of the present application, the melting temperature is 1300°C-1650°C, and the melting time is 1h-24h. In the preparation method of the ion sieve of the present application, the melting temperature can be 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C or a value within the range formed by any two of the above values as endpoints. In the preparation method of the ion sieve of the present application, the melting time can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 15h, 17h, 20h, 21h, 24h or a value within the range formed by any two of the above values as endpoints.
[0084] In the preparation method of the ion sieve of the present application, the annealing temperature is 400°C-450°C, and the annealing time is 12h-24h. In the preparation method of the ion sieve of the present application, the annealing temperature can be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or a value within the range formed by any two of the above values as endpoints. In the preparation method of the ion sieve of the present application, the annealing time can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or a value within the range formed by any two of the above values as endpoints.
[0085] In a third aspect, the present application provides a composite salt bath additive, which is a mesh container and an alkali metal ion adsorbent filled in the mesh container, and the alkali metal ion adsorbent is an ion sieve as described above or an ion sieve prepared by the preparation method of the above ion sieve; the mesh of the mesh container is above 0.15 mm.
[0086] In some embodiments of the present application, the filling rate of the alkali metal ion adsorbent relative to the volume of the mesh container is 20%-80%. In some embodiments of the present application, the filling rate of the alkali metal ion adsorbent relative to the volume of the mesh container can be 20%, 30%, 40%, 50%, 60%, 70%, 80% or a value within the range formed by any two of the above values as endpoints. Here, the filling rate of the alkali metal ion adsorbent relative to the volume of the mesh container refers to the value (%) calculated as the ratio of the volume of the alkali metal ion adsorbent to the volume of the mesh container.
[0087] In some embodiments of the present application, the alkali metal ions adsorbed by the alkali metal ion adsorbent are lithium ions. In some embodiments of the present application, the alkali metal ions adsorbed by the alkali metal ion adsorbent may also be sodium ions or lithium ions and sodium ions. In some embodiments of the present application, when the alkali metal ions with a small radius are lithium ions, the adsorbed alkali metal ions are preferably lithium ions, and when the alkali metal ions with a small radius are sodium ions, the adsorbed alkali metal ions are preferably sodium ions.
[0088] In some embodiments of the present application, the material of the mesh container is not particularly limited in the present application, as long as it does not react with the components in the salt bath; it can be a stainless steel container, a metal container, etc., preferably a material of SUS304, SUS316, etc., and preferably a metal selected from titanium materials, etc. The present application does not particularly limit the specific structure of the mesh container, as long as it contains a mesh. The stainless steel container can be a stainless steel cage. The mesh container described in the present application can be a wire mesh container, a perforated metal container, a metal mesh container, etc., preferably a wire mesh container.
[0089] In some embodiments of the present application, the mesh size of the mesh container is greater than 0.15 mm, preferably greater than 0.18 mm, and more preferably greater than 0.20 mm.
[0090] In some embodiments of the present application, the shape of the alkali metal ion adsorbent filled in the mesh container is not particularly limited, and alkali metal ion adsorbents in various shapes such as plate, rod, block, granule, agglomerate, flake, powder, etc. can be used. The size of the shape is not particularly limited, and it is regulated according to the size of the mesh of the actual mesh container so that it does not flow out of the mesh container and contaminate the salt bath.
[0091] In a fourth aspect, the present application provides the use of the ion sieve as described above, or the ion sieve prepared by the preparation method of the ion sieve as described above, or the composite salt bath additive as described above in salt bath purification.
[0092] The present application does not particularly limit the type of salt bath, as long as it contains lithium ions, wherein the impurity ions are mainly lithium ions; for example, it can be a salt bath containing NaNO3 in the presence of lithium ions, a salt bath containing KNO3, or a mixed salt bath containing NaNO3 and KNO3.
[0093] In a fifth aspect, the present application provides a method for using the ion sieve as described above or the ion sieve prepared by the preparation method of the ion sieve as described above, comprising:
[0094] Step 1): providing a salt bath to be purified, wherein the salt bath contains lithium ions; wherein the impurity ions are mainly lithium ions;
[0095] Step 2): adding the ion sieve to the salt bath to be purified;
[0096] Step 3): After the ion sieve has reacted in the salt bath to be purified for a certain period of time, it is taken out.
[0097] In the method for using the ion sieve of the present application, in step 1), the concentration of lithium ions is 50ppm-400ppm; preferably 50ppm-200ppm, more preferably 50ppm-100ppm. For example, the concentration of lithium ions can be 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 120ppm, 140ppm, 150ppm, 160ppm, 170ppm, 180ppm, 190ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm or a value within the range formed by any two of the above values as endpoints.
[0098] In the method for using the ion sieve of the present application, the salt bath in step 1) also contains sodium salt and / or potassium salt; preferably NaNO3 and / or KNO3. In some embodiments of the present application, the salt bath may contain a combination of NaNO3 and KNO3, or may be pure NaNO3 or pure KNO3. Among them, the combination of NaNO3 and KNO3 can be selected according to the desired application, and the concentrations of NaNO3 and KNO3 in the salt bath can be balanced according to the composition of the glass material for ion exchange, thereby providing sufficient CS and DOL for the glass material; the glass material comprises lithium-containing glass-ceramics and lithium aluminum-silicon glass; further, the crystalline phase of the lithium-containing glass-ceramics comprises one or more of petalite, lithium disilicate, lithium monosilicate, and eucryptite; it should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0099] In the method for using the ion sieve of the present application, the temperature of the salt bath in step 1) is 350°C-550°C; preferably 380°C-530°C; more preferably 380°C-500°C. For example, the salt bath temperature can be 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or a value within the range formed by any two of the above values as endpoints.
[0100] In the method for using the ion sieve of the present application, the amount of the ion sieve added in step 2) is 0.50wt%-5.00wt% of the mass of the salt bath to be purified; preferably 1.00wt%-5.00wt% of the mass of the salt bath to be purified. For example, the amount of the ion sieve added can be 0.50wt%, 0.60wt%, 0.70wt%, 0.80wt%, 0.90wt%, 1.00wt%, 1.30wt%, 1.50wt%, 1.60wt%, 1.80wt%, 2.00wt%, 2.30wt%, 2.50wt%, 2.70wt%, 3.00wt%, 3.50wt%, 4.00wt%, 4.50wt%, 5.00wt% of the mass of the salt bath to be purified, or a value within the range formed by any two of the above values as endpoints.
[0101] In the method for using the ion sieve of the present application, the reaction time of the ion sieve in the salt bath to be purified in step 3) is 3h-24h; preferably 6h-24h; more preferably 8h-16h. For example, the reaction time of the ion sieve in the salt bath to be purified can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 14h, 16h, 18h, 20h, 21h, 22h, 23h, 24h or a value within the range formed by any two of the above values as endpoints.
[0102] In the method for using the ion sieve of the present application, when the lithium ion concentration of the salt bath to be purified is 50ppm-400ppm, the amount of the ion sieve added is 0.50wt%-5.00wt% of the mass of the salt bath to be purified, and after the reaction time in the salt bath to be purified is 3h-24h, the absorption efficiency of the ion sieve is 50%-95%, preferably 53%-95%. For example, the absorption rate of the ion sieve can be 50%, 53%, 56%, 58%, 60%, 65%, 70%, 75%, 78%, 80%, 88%, 90%, 95% or a value within the range formed by any two of the above values as endpoints.
[0103] In a sixth aspect, the present application provides a method for using the composite salt bath additive as described above, comprising:
[0104] Step 1): providing a salt bath to be purified, wherein the salt bath contains lithium ions;
[0105] Step 2): adding a composite salt bath additive to the salt bath to be purified;
[0106] Step 3): After the composite salt bath additive has reacted in the salt bath to be purified for a certain period of time, it is taken out.
[0107] In the method for using the composite salt bath additive of the present application, in step 1), the concentration of lithium ions is 50ppm-400ppm; preferably 50ppm-200ppm, more preferably 50ppm-100ppm. For example, the concentration of lithium ions can be 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 120ppm, 140ppm, 150ppm, 160ppm, 170ppm, 180ppm, 190ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm or a value within the range formed by any two of the above values as endpoints.
[0108] In the method for using the composite salt bath additive of the present application, the salt bath in step 1) also contains sodium salt and / or potassium salt; preferably NaNO3 and / or KNO3. In some embodiments of the present application, the salt bath may contain a combination of NaNO3 and KNO3, or may be pure NaNO3 or pure KNO3. Among them, the combination of NaNO3 and KNO3 can be selected according to the desired application, and the concentrations of NaNO3 and KNO3 in the salt bath can be balanced according to the composition of the glass material undergoing ion exchange, thereby providing the glass material with sufficient CS (surface compressive stress) and DOL (depth of compressive stress layer); the glass material comprises lithium-containing glass-ceramics and lithium aluminum-silicon glass; further, the crystalline phase of the lithium-containing glass-ceramics comprises one or more of petalite, lithium disilicate, lithium monosilicate, and eucryptite; it should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0109] In the method for using the composite salt bath additive of the present application, the temperature of the salt bath in step 1) is 350°C-550°C; preferably 380°C-530°C; more preferably 380°C-500°C. For example, the salt bath temperature can be 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or a value within the range formed by any two of the above values as endpoints.
[0110] In the method for using the composite salt bath additive of the present application, the amount of the alkali metal ion adsorbent added to the composite salt bath additive in step 2) is 0.5wt%-5.0wt% of the mass of the salt bath to be purified; preferably 1.00wt%-5.00wt% of the mass of the salt bath to be purified. For example, the amount of the alkali metal ion adsorbent added to the composite salt bath additive can be 0.50wt%, 0.60wt%, 0.70wt%, 0.80wt%, 0.90wt%, 1.00wt%, 1.30wt%, 1.50wt%, 1.60wt%, 1.80wt%, 2.00wt%, 2.30wt%, 2.50wt%, 2.70wt%, 3.00wt%, 3.50wt%, 4.00wt%, 4.50wt%, 5.00wt% of the mass of the salt bath to be purified, or a value within the range formed by any two of the above values as endpoints.
[0111] In the method for using the composite salt bath additive of the present application, the reaction time of the composite salt bath additive in the salt bath to be purified in step 3) is 3h-24h; preferably 6h-24h; more preferably 8h-16h. For example, the reaction time of the composite salt bath additive in the salt bath to be purified can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 14h, 16h, 18h, 20h, 21h, 22h, 23h, 24h or a value within the range formed by any two of the above values as endpoints.
[0112] In the method for using the composite salt bath additive of the present application, when the lithium ion concentration of the salt bath to be purified is 50ppm-400ppm, the addition amount of the alkali metal ion adsorbent in the composite salt bath additive is 0.50wt%-5.00wt% of the mass of the salt bath to be purified, and after the reaction time in the salt bath to be purified is 3h-24h, the absorption efficiency of the composite salt bath additive is 50%-95%, preferably 53%-95%. For example, the absorption rate of the composite salt bath additive can be 50%, 53%, 56%, 58%, 60%, 65%, 70%, 75%, 78%, 80%, 88%, 90%, 95% or a value within the range formed by any two of the above values as endpoints.
[0113] In the seventh aspect, the present application also provides a chemical strengthening process for lithium-containing microcrystalline glass, which includes the following steps: adding the ion sieve described above in the present application or the ion sieve prepared by the above-mentioned ion sieve preparation method or the above-mentioned composite salt bath additive to the salt bath for chemically strengthening the lithium-containing microcrystalline glass.
[0114] Test method:
[0115] <Density Test>
[0116] The density of the ion sieve was tested using an electronic density balance SD-200L from ALFA MIRAGE of Japan, and the test principle was the "Archimedes drainage method".
[0117] <Measurement of the lithium ion concentration in the salt bath>
[0118] An appropriate amount of molten salt bath to be measured for lithium ion concentration was taken out of the strengthening furnace. After the molten salt bath cooled, 0.25 g of the cooled solid substance was accurately weighed into a 100 mL glass beaker, dissolved with an appropriate amount of deionized water, filtered through a slow filter paper into a 100 mL volumetric flask, 1 mL of 18 wt% hydrochloric acid aqueous solution was added to the volumetric flask, and then deionized water was added to the volumetric flask to make up the volume and shaken well. The absorbance was measured using an atomic absorption spectrophotometer AA-6880, and then the lithium ion concentration in the salt bath was measured using the corresponding standard curve.
[0119] <Measurement of the lithium ion absorption rate of the ion sieve>
[0120] Step S1: In a clean stainless steel crucible, 700 g of potassium nitrate, 300 g of sodium nitrate and 1 g of lithium nitrate were mixed and melted at a temperature of 480 °C to prepare a salt bath with a lithium ion concentration of 100 ppm, and the concentration was denoted as C1;
[0121] Step S2: 50 mm × 50 mm × 0.7 mm ion sieve with a polished surface accounting for 1.00 wt% of the mass of the salt bath was added to the mixed salt bath described in Step S1. After holding the reaction at 480 °C for 8 h, an appropriate amount of the salt bath was taken, and the lithium ion concentration was detected using the method in <Measurement of the lithium ion concentration in the salt bath>, denoted as C2;
[0122] The lithium ion absorption rate of the ion sieve = (C1 - C2) / C1 × 100%.
[0123] <XRD test>
[0124] The initial ion sieve and the ion sieve after reacting in a 480 °C salt bath with a lithium ion concentration of 100 ppm for 8 h were respectively ground into fine powder using a pulverizer, and the particle size was less than 75 μm. Then, an X-ray diffractometer was used to test it to obtain the XRD diffraction peak curve. The XRD diffraction data was analyzed using JADE software.
[0125] The X-ray diffractometer used in this application was Shimadzu XRD-6100. The range of the incident angle for the test was 2θ = 10 - 80°, the scanning speed was 6° / min, the working voltage was 40 KV, and the working current was 30 mA.
[0126] <Stability determination>
[0127] The crystal form of the ion sieve after absorbing lithium ions for 8 hours in a 480°C salt bath with a lithium ion concentration of 100 ppm is compared with the crystal form before absorbing lithium ions. If a significant change occurs, the ion sieve is considered to be unstable; otherwise, the ion sieve is considered to be stable.
[0128] <Test for crystal content in ion sieve>
[0129] The crystal content in the ion sieve is measured by the proportion of the crystal phase peak area in the XRD spectra of the initial ion sieve and the ion sieve after absorbing lithium ions in the salt bath, that is, the ratio of the crystal phase peak area based on the XRD spectrum fitting and the total peak area of the fitting is the crystal content.
[0130] In the present invention, an X-ray diffractometer is used to test the initial ion sieve and the ion sieve after absorbing lithium ions in a salt bath, and the X-ray diffractometer test result file (RAW format) is imported into the X-ray diffraction data Rietveld refinement software (such as Jade) for fitting and calculation.
[0131] <Determination of the status of fallen fragments>
[0132] An ion sieve with a size of 50mm×50mm×0.7mm and a polished surface is added to the salt bath to be purified. The amount of the plate-shaped ion sieve added is 1.0wt% of the mass of the salt bath to be purified. The salt bath is a salt bath of 700g KNO3, 300g NaNO3 and 1g LiNO3, and the concentration of lithium ions is 100ppm. After reacting at 480°C for 8 hours, it is taken out. The state of the ion sieve after purification in the salt bath is observed. If no fragments fall off, the state of the falling fragments is recorded as no fragments fall off; if fragments fall off, the size of the falling fragments is measured.
[0133] Method for measuring the size of detached fragments: collect the detached fragments generated by the ion sieve, weigh them and record them as W1, sieve them with a 100-mesh sieve, and the weight of the residue is recorded as W2. If W2 / W1=100%, it means that the size of the fragments detached from the above ion sieve is greater than 0.15mm, and it is recorded as the size of the detached fragments is greater than 0.15mm; if W2 / W1 is less than 100%, it means that the size of the fragments detached from the above ion sieve is less than 0.15mm, and it is recorded as the size of the detached fragments is less than 0.15mm.
[0134] <Appearance test>
[0135] The selected microcrystalline glass sheet was cleaned and dried, the sample was placed on a stage, and photographed using a Canon entry-level digital camera to obtain an appearance image of the glass sheet surface.
[0136] <Pianguan Microscope Test>
[0137] The selected microcrystalline glass sheet was ultrasonically cleaned and dried, the sample was placed on a stage, and photographed using a polarizing microscope of model AxioLab5 to obtain a surface polarizing microscope image of the glass sheet surface.
[0138] The present application is described below by means of specific embodiments:
[0139] Example 1
[0140] The raw materials were accurately weighed according to the following proportions: SiO2 57.0 mol%, Al2O3 3.0 mol%, Na2O4 0.0 mol%; the total mass of the raw materials was 1 kg, and then melted at 1450° C. for 5 h to form molten glass.
[0141] The glass liquid is injected into a mold for molding, annealed at 420° C. for 12 h, and then cut and polished to obtain an ion sieve with a size of 50 mm×50 mm×0.7 mm and a polished surface.
[0142] The plate-like ion sieves obtained above were subjected to density tests respectively; then the plate-like ion sieves were added to the salt bath to be purified, the amount of the plate-like ion sieve added was 1.0wt% of the mass of the salt bath to be purified, the salt bath was a salt bath of 700g KNO3, 300g NaNO3 and 1g LiNO3, and the concentration of lithium ions was 100ppm; after reacting at 480°C for 8 hours, they were taken out; the lithium ion absorption rate of the ion sieve was tested, and its stability and the state of detached fragments were determined, and the crystal content was tested; the results are shown in Tables 3-4.
[0143] Example 2-11
[0144] Except for adjusting the raw material ratio as shown in Table 3, the rest is the same as Example 1.
[0145] Comparative Examples 1-6
[0146] Except for adjusting the raw material ratio as shown in Table 4, the rest is the same as Example 1.
[0147] Comparative Example 7
[0148] The process is the same as in Example 1 except that the temperature for absorbing lithium ions in the salt bath is 565°C.
[0149] In addition, a lithium aluminum silicon substrate glass having a composition of SiO2 70 mol%, Al2O3 4.15 mol%, Li2O 20.68%, P2O5 1.02%, ZrO2 2.66%, Na2O 0.29%, K2O 0.09%, CaO 0.80 mol%, and B2O3 0.31 mol% was placed in a mixed salt bath of 70 wt% NaNO3 and 30 wt% KNO3 at 480° C., and the ion sieves of Example 2 and Comparative Example 4 were added respectively, and the amount of the ion sieve added was 1 wt% of the mass of the mixed salt bath. After the chemical strengthening treatment for 8 hours, the surface appearance of the chemically strengthened glass obtained after the chemical strengthening treatment was observed using a polarizing microscope, and the obtained surface appearance is shown in the figure below. Figure 9-10 shown.
[0150] In addition, the ion sieve of Example 4 was installed in a 316 stainless steel cage A (260 mm long, 110 mm wide, and 50 mm high) with different meshes to prepare composite salt bath additives A1-A4, and added to the salt bath to be purified, and reacted at 480°C for 8 hours; then the lithium ion absorption rate of the ion sieve was tested. The meshes of the 316 stainless steel cage A were 20 mesh, 80 mesh, 100 mesh, and 120 mesh, respectively; the salt bath was a salt bath of 700 g KNO3, 300 g NaNO3, and 1 g LiNO3, and the concentration of lithium ions was 100 ppm; relative to the volume of the 316 stainless steel cage A, the filling rate of the ion sieve of Example 4 was 30%, and the amount thereof added was 0.8 wt% of the mass of the salt bath to be purified. The results are shown in Table 5 below.
[0151] The ion sieve of Example 7 was installed in a 316 stainless steel cage B (100 mm long, 100 mm wide, 20 mm high) with different meshes to prepare composite salt bath additives B1-B4, and added to the salt bath to be purified, and reacted at 480°C for 8 hours; then the lithium ion absorption rate of the ion sieve was tested. The meshes of the 316 stainless steel cage B were 20 mesh, 80 mesh, 100 mesh and 120 mesh respectively; the salt bath was a salt bath of 700 g KNO3, 300 g NaNO3 and 1 g LiNO3, and the concentration of lithium ions was 100 ppm; relative to the volume of the 316 stainless steel cage B, the filling rate of the ion sieve of Example 7 was 40%, and the amount added was 1.0 wt% of the mass of the salt bath to be purified. The results are shown in Table 6 below.
[0152] In addition, a lithium aluminum silicon substrate glass with a composition of SiO2 70mol%, Al2O3 4.15mol%, Li2O 20.68%, P2O5 1.02%, ZrO2 2.66%, Na2O 0.29%, K2O 0.09%, CaO 0.80mol%, and B2O3 0.31mol% was placed in a mixed salt bath of 70wt% NaNO3 and 30wt% KNO3 at 480°C, and a composite salt bath additive A3 or a composite salt bath additive B3 was added respectively, and the addition amount of the ion sieve in the composite salt bath additive A3 or the composite salt bath additive B3 was 1.2wt% of the mass of the mixed salt bath. After the chemical strengthening treatment for 8 hours, the surface appearance of the chemically strengthened glass obtained after the chemical strengthening treatment was observed using a polarizing microscope, and the obtained surface appearance is shown in the figure below. Figure 11-12 shown.
[0153] Table 3. Composition and related performance parameters of the ion sieves of Examples 1-11
[0154]
[0155]
[0156] Table 4. Composition and related performance parameters of the ion sieves in Comparative Examples 1-7
[0157]
[0158]
[0159] Table 5. Composite salt bath additives and their lithium ion absorption rate
[0160] 316 stainless steel cage A (mesh) Lithium ion absorption rate (%) Compound salt bath additive A1 20 63.50 Compound salt bath additive A2 80 62.68 Compound salt bath additive A3 100 61.35 Compound salt bath additive A4 120 55.29
[0161] Table 6. Composite salt bath additives and their lithium ion absorption rate
[0162] 316 stainless steel cage B (mesh) Lithium ion absorption rate (%) Compound salt bath additive B1 20 72.29 Compound salt bath additive B2 80 71.59 Compound salt bath additive B3 100 70.38 Compound salt bath additive B4 120 61.23
[0163] (1) The crystal content of the ion sieve prepared in the examples of the present application before and after absorbing lithium ions is less than 10wt%, and no crystal transformation occurs. The composition and structure of the ion sieve are stable, no fragments fall off, and it has a high lithium ion absorption efficiency. Comparative Examples 1-6 The ion sieves prepared outside the formula range of the present application have a very large change in crystal content before and after absorbing lithium ions, and a crystal transformation occurs, such as Figure 1 and Figure 2 shown.
[0164] (2) Figure 3 This is the appearance of the ion sieve in Example 1 after absorbing lithium ions in a 480° C. salt bath for 8 hours; Figure 4This is the appearance of the ion sieve in Example 6 after absorbing lithium ions in a 480° C. salt bath for 8 hours; Figure 5 This is the appearance of the ion sieve in Comparative Example 2 after absorbing lithium ions in a 480°C salt bath for 8 hours; Figure 6 This is the appearance of the ion sieve in Comparative Example 3 after absorbing lithium ions in a 480°C salt bath for 8 hours; Figure 7 This is the appearance of the ion sieve in Comparative Example 5 after absorbing lithium ions in a 480° C. salt bath for 8 hours; Figure 8 This is the appearance of the ion sieve in Comparative Example 6 after absorbing lithium ions in a 480°C salt bath for 8 hours. Fig. 9 This is a polarizing microscope image of the surface of the chemically strengthened glass obtained after the ion sieve of Example 2 is added to the salt bath; Fig.10 This is a polarizing microscope image of the surface of the chemically strengthened glass obtained after adding the ion sieve of Comparative Example 4 to the salt bath. Fig. 9 It can be seen that there is no detached fragment of ion sieve attached to the surface of chemically strengthened glass; Fig.10 It can be seen that there are many detached fragments of ion sieve attached to the surface of chemically strengthened glass.
[0165] (3) As can be seen from Tables 5-6, when the ion sieve is installed in a 316 stainless steel cage with a mesh size of less than 100 mesh, i.e., a mesh size of more than 0.15 mm, for salt bath purification, the mesh size of the 316 stainless steel cage has little effect on the lithium ion absorption rate of the ion sieve, and basically does not affect the actual effect of the ion sieve on salt bath purification; and it has a high adsorption efficiency for lithium ions. Fig.11 This is a polarizing microscope image of the surface of the chemically strengthened glass obtained after adding the composite salt bath additive A3 to the salt bath; Fig.12 This is a polarizing microscope image of the surface of chemically strengthened glass obtained after adding the composite salt bath additive B3 to the salt bath. Figure 11-12 It can be seen that there are no detached fragments of the ion sieve attached to the surface of the chemically strengthened glass.
[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.
Claims
1. An ion sieve, characterized in that: The ion sieve comprises the following components in terms of molar percentage of oxide: SiO2 45.0-64.0mol%; Al2O3 2.0-16.0mol%; Na2O 34.0-45.0mol%; ZrO2 0-3.0mol%; Y2O3 0-2.0mol%; Wherein, after the ion sieve absorbs lithium ions for 0.5h-24h in a salt bath at a temperature of 350°C-550°C, the crystal form of the ion sieve does not change.
2. The ion screen according to claim 1, characterized in that: After the ion sieve undergoes sodium-lithium ion exchange at any ratio within the range of 350° C.-550° C., the content of crystals in the ion sieve is less than 10 wt %.
3. The ion screen according to claim 1, characterized in that: The density of the ion sieve is 2.40 g / cm 3 -2.55g / cm 3 .
4. The ion screen according to claim 1, characterized in that: The ion sieve does not shed fragments after absorbing lithium ions for 0.5h-24h in a salt bath at 350°C-550°C.
5. The ion sieve according to any one of claims 1 to 4, characterized in that: The concentration of lithium ions in the salt bath is 50ppm-400ppm.
6. The method for preparing the ion sieve according to any one of claims 1 to 5, characterized in that: include: The raw material components are selected according to the composition of the ion sieve, mixed, melted and formed, and then annealed to obtain the ion sieve.
7. The preparation method according to claim 6, characterized in that: The melting temperature is 1300°C-1650°C, and the melting time is 1h-24h; Preferably, the annealing temperature is 400° C.-450° C., and the annealing time is 12 h-24 h.
8. A composite salt bath additive, comprising a mesh container and an alkali metal ion adsorbent filled in the mesh container, wherein the alkali metal ion adsorbent is the ion sieve according to any one of claims 1 to 5 or an ion sieve prepared by the method for preparing the ion sieve according to any one of claims 6 to 7; and the mesh of the mesh container is not less than 0.15 mm.
9. The composite salt bath additive according to claim 8, characterized in that: The mesh container is at least one of a stainless steel container and a metal container.
10. The composite salt bath additive according to claim 8, characterized in that: The filling rate of the alkali metal ion adsorbent is 20%-80% relative to the volume of the mesh container.
11. Use of the ion sieve according to any one of claims 1 to 5 or the ion sieve prepared by the preparation method of the ion sieve according to any one of claims 6 to 7 or the composite salt bath additive according to any one of claims 8 to 9 in salt bath purification.
12. The method for using the composite salt bath additive according to any one of claims 8 to 10, characterized in that: Includes steps: providing a salt bath to be purified, wherein the salt bath contains lithium ions; adding a composite salt bath additive to the salt bath to be purified; After the composite salt bath additive has reacted in the salt bath to be purified for a certain period of time, taking it out; Preferably, the amount of the alkali metal ion adsorbent in the composite salt bath additive is 0.5wt%-5.0wt% of the mass of the salt bath to be purified; Preferably, the temperature of the salt bath is 350°C-550°C; Preferably, the concentration of lithium ions in the salt bath is 50ppm-400ppm; Preferably, the composite salt bath additive reacts in the salt bath to be purified for 3 h to 24 h; Preferably, when the lithium ion concentration of the salt bath to be purified is 50ppm-400ppm, the added amount of the alkali metal ion adsorbent is 0.50wt%-5.00wt% of the mass of the salt bath to be purified, and the filling rate of the alkali metal ion adsorbent relative to the volume of the mesh container is 20%-80%; the reaction time of the composite salt bath additive in the salt bath to be purified is 3h-24h, and the absorption efficiency of the composite salt bath additive is 50%-95%.
Citation Information
Patent Citations
Boron-free phosphorus-free high-stability ion sieve and application thereof
CN112645610A
Method for recovering composition of molten salt composition and method for producing chemically strengthened glass
CN115259690A
Salt bath additive and preparation method thereof
CN115806394A
High-temperature-resistant ion sieve easy to store
CN118454635A
Cited By
High-temperature-resistant and High-stability Ion Sieve and Preparation Method and Application thereof
US20250114781A1
